UMP organised golf charity event to raise fund for MyGift scholarship programme - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) Golf Club hosted UMP Golf Charity Tournament on September 3, 2016 which was aimed at raising fund for scholarships under its MyGift programme.